The Impact of Nursing Interventions on Patient Care Outcomes: A Systematic Review of Evidence-Based Practices and Holistic Approaches - Alotaibi, Amani Nasser; Alanazi, Eman Mufadhi; Alsubaie, Hanadi Shafi; Alotaibey, Moneerah Hmood (Journal of Posthumanism, 2024)
This systematic review examines the impact of nursing interventions on patient care outcomes across diverse healthcare settings. Nursing plays a pivotal role in delivering evidence-based, patient-centered care that integrates clinical expertise, compassion, and holistic approaches. By systematically reviewing studies published between 2016 and 2024, this paper evaluates the effectiveness of nursing practices in improving patient safety, quality of care, and overall satisfaction. Key findings highlight the significance of interventions in areas such as medication management, patient education, pain control, infection prevention, and psychosocial support. The review also underscores the importance of holistic care approaches, addressing physical, emotional, social, and spiritual dimensions of health. Despite challenges such as staffing shortages, workload pressures, and variability in training, evidence supports the critical role of nursing in enhancing health outcomes. The paper concludes with recommendations for strengthening nursing practices through continuous education, integration of technology, and interdisciplinary collaboration.